Pengaruh Konsentrasi Starter Acetobacter xylinum dan Lama Fermentasi Terhadap Kualitas Produk Nata de coco - Maulida Nurdin, Gaby; Nurhidayah (Universitas Sulawesi Barat, 2023)
Nata de coco is an alternative food source that uses Acetobacter xylinum in the fermentation process. However, the high rate of nata de coco product failures is still commonly encountered due to the inadequate concentration of the starter and the fermentation duration. This study aims to determine whether there is an effect of starter Acetobacter xylinum and duration of fermentation on the quality of nata de coco. The research is of a quantitative experimental type. The research method employs a Completely Randomized Design (CRD) with two factors, namely the concentration of starter Acetobacter xylinum (10%, 15%, and 20%) and fermentation time (6 days, 10 days, and 14 days) with 9 treatment combinations and 3 replications. Data analysis used ANOVA followed by DMRT. The results showed that the combination of starter and fermentation time did not have a significant effect on the thickness and yield of nata de coco, but had a significant effect if tested based on a single factor. The best organoleptic results vary according to their parameters (color, aroma, texture, and taste), depending on the specific combination of Acetobacter xylinum starter concentration and fermentation duration treatment that has a significant effect. Keywords— Acetobacter xylinum, fermentation time, nata de coco